2005
DOI: 10.2105/ajph.2004.043059
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Uncertainty: Contested Science and the Protection of the Public’s Health and Environment

Abstract: Opponents of public health and environmental regulations often try to "manufacture uncertainty" by questioning the validity of scientific evidence on which the regulations are based. Though most identified with the tobacco industry, this strategy has also been used by producers of other hazardous products. Its proponents use the label "junk science" to ridicule research that threatens powerful interests.This strategy of manufacturing uncertainty is antithetical to the public health principle that decisions be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
173
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(184 citation statements)
references
References 32 publications
0
173
0
5
Order By: Relevance
“…These causes include mixed messages and misinformation from various sources, including the deliberate “manufacturing” of scientific uncertainty in the service of other goals. 51 …”
Section: Implications For Research and Clinical Practicementioning
confidence: 99%
“…These causes include mixed messages and misinformation from various sources, including the deliberate “manufacturing” of scientific uncertainty in the service of other goals. 51 …”
Section: Implications For Research and Clinical Practicementioning
confidence: 99%
“…Scientific uncertainty is the strategy of questioning the underlying science in order to prevent regulation [58]. In this study the food industry submissions to government select committees questioned the underlying science on the causes and prevention of obesity, thus creating uncertainty around the optimal evidence based policy tool.…”
Section: Vested Interests and Uncertaintymentioning
confidence: 99%
“…In this study the food industry submissions to government select committees questioned the underlying science on the causes and prevention of obesity, thus creating uncertainty around the optimal evidence based policy tool. Michaels and Monforton highlighted the same tactic by aspirin manufacturers and the tobacco industry seeking to delay the requirement for specific warning labels in the 1980s, observing that the tactic is now so commonly used in the United States that is unusual for the science behind a proposed public health or environmental regulation not to be challenged by an industry group [58].…”
Section: Vested Interests and Uncertaintymentioning
confidence: 99%
“…Corporate decision makers strived to achieve control over governmental regulation of tobacco 6 and food 7 to lower governmental classification of carcinogenic potential of their products 13 and to persuade governmental agencies to adopt permissible threshold concentrations of industrial products that are significantly higher than those reported to be hazardous to health. [14][15][16][17][18] They attempt to throw doubt on scientific evidence, [19][20][21][22][23] thus influencing not only regulatory agencies but also public opinion, courts, and juries. When the hazards of the products cannot be denied, they use administrative or court actions to delay implementation of regulation.…”
Section: Introductionmentioning
confidence: 99%